3x-8t=-8

Simple and best practice solution for 3x-8t=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-8t=-8 equation:


Simplifying
3x + -8t = -8

Reorder the terms:
-8t + 3x = -8

Solving
-8t + 3x = -8

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-8t + 3x + -3x = -8 + -3x

Combine like terms: 3x + -3x = 0
-8t + 0 = -8 + -3x
-8t = -8 + -3x

Divide each side by '-8'.
t = 1 + 0.375x

Simplifying
t = 1 + 0.375x

See similar equations:

| 5/6*-6/7 | | 2x+7+10=11x | | 1.7(r+1)=6.8 | | 9-4(2x-1)=45-4x | | (-3-7)+(4+7)= | | -152=4(-8+5m) | | b/9=a | | b/9=8 | | 38n+1=25 | | 3=-4/w-7 | | 3(-5a+9)-2(4a+6)= | | 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 | | 16Y-7y=500 | | 4x-3+0=-3x-4 | | ((12k^2h)-(3kh^2))/3kh | | 0.25(8-4p)+2p=12 |

Equations solver categories